THU0477 Genetic Risk Factors for Fibromyalgia Associated Symptoms/Syndromes and Disease Severity. (10th June 2014) - Rodriguez-Rodriguez, L.; Lamas, J.R.; Jover, J.A.; Baena, S.; Olano, E.; Collado, A.; Rivera, J.; Fernandez-Gutierrez, B.
Abstract : Background: Fibromyalgia (FM) is a condition characterized by chronic widespread pain associated to multiple symptoms, including fatigue, sleep disturbances, cognitive dysfunction, and depressive episodes. In recent years, many candidate gene association studies have been designed and carried out to identify the genes associated with FM. However, the study of the genetic factors associated to disease severity or to the presence of coexisting comorbidities, and therefore, potentially useful as predictors of disease outcome, is a relatively unexplored field. Objectives: To study in FM patients the genetic risk factors involved in the presence of syndromes and symptoms associated with this disease, and/or severity. Methods: We included Spanish Caucasian patients diagnosed with FM according to 1990 ACR criteria. Fist, we used a discovery cohort (DC) of 564 patients, recruited from 15 centers throughout the Spanish geography. Subsequently, we used a replication cohort (RC) of 397 patients from the DNA Bank for Genetic Research in FM and Chronic Fatigue Syndrome of the FF Foundation and from the National DNA Bank (Salamanca, Spain). In the DC we studied the association between 320 single nucleotide polymorphisms (SNPs), located in 22 loci, and the presence of symptoms and syndromes associated with FM (depression, headache, sleep disorders, myofascial syndrome, irritable bowel syndrome, chronic fatigue, vertiginous syndrome, chronic cystitis, and sicca syndrome) and disease severity, using the FIQ (Fibromyalgia Impact Questionnaire) and the HADS (Hospital Anxiety and Depression Scale). In the RC, we studied those SNPs and those variables that were associated in the discovery cohort. As the dependent variables were dichotomous or continuous, linear or logistic regressions were performed, respectively, to study the genetic association, using an additive model of effects. The odds ratio (OR), with 95% confidence intervals [95% CIs], was used to assess the strength of association between genotypes and the main dichotomous variables. Analyses were adjusted for sex and time from the onset of pain symptoms. P values were adjusted for the number of main variables and a cutoff of 0.05 was established to select those SNPs to replicate in the RC. DC and RC results were pooled using meta-analysis techniques. P value was corrected considering the number of linkage disequilibrium blocks in which the analyzed SNPs were included. Results: In the DC, we observed 10 SNPs with an adjusted p-value lower that 0.05: rs4760750, rs4760816, rs2171363 (associated to sleep disturbances), rs174696, rs10171225, rs3771863 (associated to sicca syndrome), rs2422148, rs2216307 (associated to vertigo), and rs12654778, rs10434128 (associated to HADS depression). After replication in the RC and pooling the results from both cohorts, only the rs3771863 variant, from the TACR1 gene, showed a significant association with a lower risk of sicca syndrome (adjusted OR 0.56 [95% CI 0.42 - 0.76], p=0.00022). Conclusions: TACR1 gene could play a role in the development of sicca syndrome in FM patients. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5542